The Effects of Cannabis Use Frequency and Episodic Specificity Training on the Recall of Specific and Rewarding Events - Sofis, Michael J.; Lemley, Shea M.; Budney, Alan J. (Frontiers in Psychiatry, 2021)
Background: Growing evidence implicates subjective episodic memory, the retrieval of detailed, and personally relevant past events, as a marker of cognitive vulnerability in mental disorders. Frequent and problematic cannabis use is associated with deficits in objective episodic memory (verbal memory), but the relationship between subjective episodic memory deficits and frequency of cannabis use is unknown. Further, whether a brief intervention designed to enhance the specificity of event retrieval, such as the Episodic Specificity Induction (ESI), might effectively target such deficits among regular cannabis users is unexamined. This study was designed to investigate subjective episodic memory as a potential marker of cognitive vulnerability among frequent cannabis users. Methods: Active cannabis users (n=133) recruited from Amazon Mechanical Turk or Qualtrics Panels were randomized to receive an ESI-control or ESI session and were separated into those who used cannabis 1-25 days in the past month (low to moderate frequency group) and those who used 26-30 days (high frequency group), which facilitated a low to moderate use/ESI-control group (n=78), low to moderate use/ESI group (n=15), high-use/ESI-control group (n=20), and high-use/ESI group (n=20). Following the ESI or ESI-control intervention, participants selected four, positive events from the prior day, described the who, what, and where of the events, and rated how specific (vividness) and rewarding (enjoyable, importance, and exciting) each event was on a 0-100 scale. Four two-way ANCOVAs (demographics and problematic cannabis use covariates) were performed to examine the effects of frequency of cannabis use group and ESI group on the specificity and reward ratings. Results: Lower vividness and excitement ratings were reported for those with high relative to low to moderate cannabis use frequency patterns (p < .05). Those who received ESI reported greater vividness, excitement, and importance ratings than the ESI-control group (p < .01). No significant interactions between frequency and ESI were found. Conclusion: Findings from the current exploratory study provide initial evidence suggesting that more frequent cannabis use may be associated with the retrieval of less specific and rewarding events. Further, ESI may improve such deficits. Future studies that recruit larger and more clinically serious samples of cannabis users appear warranted.